Tomato and mini-cucumber tolerance to photoperiodic injury involves photorespiration and the engagement of nighttime cyclic electron flow from dynamic LEDs - Marie, Telesphore R. J. G.; Leonardos, Evangelos Demos; Rana, Naheed; Grodzinski, Bernard (Frontiers in Plant Science, 2024)
Controlled environment agriculture (CEA) is critical for achieving year-round food security in many regions of the world. CEA is a resource-intensive endeavor, with lighting consuming a large fraction of the energy. To lessen the burden on the grid and save costs, an extended photoperiod strategy can take advantage of off-peak time-of-day options from utility suppliers. However, extending the photoperiod limits crop production morphologically and physiologically if pushed too long. Here, we present a continuous-light dynamic light-emitting diode (LED) strategy (involving changes in spectra, intensity, and timing), that overcomes these limitations. We focused on tomato, a well described photoperiodic injury–sensitive species, and mini-cucumber, a photoperiodic injury-tolerant species to first assess morphological responses under control (16-h photoperiod, unchanging spectrum), constant (24-h photoperiod, unchanging spectrum), and two variations of a dynamic LED strategy, dynamic 1 (16-h “day”, 3-h “peak”, 8-h “night” spectra) and dynamic 2 (20-h “day”, 5-h “peak”, 4-h “night” spectra). Next, we tested the hypothesis of photorespiration’s involvement in photoperiodic injury by using a leaf gas exchange coupled with chlorophyll fluorescence protocol. We further explored Adenosine triphosphate (ATP): Nicotinamide adenine dinucleotide phosphate (NADPH) ratio supply/demand responses by probing photosynthetic electron flow and proton flow with the MultispeQ instrument. We found canopy architecture can be tuned by minor variations of the same dynamic LED strategy, and we highlight dynamic 1 as the optimal choice for both tomato and mini-cucumber as it improved biomass/architecture and first-yield, respectively. A central discovery was that dynamic 1 had a significantly higher level of photorespiration than control, for both species. Unexpectedly, photorespiration was comparable between species under the same treatments, except under constant. However, preliminary data on a fully tolerant tomato genotype grown under constant treatment upregulated photorespiration similar to mini-cucumber. These results suggest that photoperiodic injury tolerance involves a sustained higher level of photorespiration under extended photoperiods. Interestingly, diurnal MultispeQ measurements point to the importance of cyclic electron flow at subjective nighttime that may also partially explain why dynamic LED strategies mitigate photoperiodic injury. We propose an ontology of photoperiodic injury involving photorespiration, triose phosphate utilization, peroxisomal H2O2-catalase balance, and a circadian external coincidence model of sensitivity that initiates programmed cell death.